The capture and the escape of neorurals. Emancipatory practices and institutional and economic discourses among southern European neorurals. - Mateus, C.; Nicoletta, G. (IV Jornadas Internacionales de Antropologia del Conflicto Urbano, 2022)
In the past decades, neorurality has often been analysed as an autonomous project enhancing alternative food production and distribution as well as re-framing imbalances between central and rural areas. At the same time, it has been highlighted how neo-rurality can also be a means for reshaping rural areas according to certain transnational defined economic strategies as well as a vehicle of rural gentrification. In order to explore this issue, we compare two different research paths on neoruraliy in order to develop conceptual tools to address a third indicative case study. The first is the case of Cooperativa Minga in Montemor-o-Novo, Portugal. A group of neorurals, aiming for the possibility of developing personal life projects, create a cooperative that works as a common financial structure. This structure facilitates the development of autonomous productive, commercial and services-directed activities of its members. In this case, the financial autonomy from State-Market institutions is presented as one of the main features for the projection of alternative life projects that criticise the hegemonic discourse on the capitalisation of rural territories and culture.The second case is the emergence of a neorural discourse in the southern territories of Italy. Here different institutions, public organisations, foundations and private entrepreneurs have articulated rurality as a possible strategy of economic development to fill the gap in central areas. Through these articulations, (images of) rurality circulates among local communities, attaching motivations and behaviour to a competition strategy constructed around the agro-touristic sector, producing/auguring a rural entrepreneurial subjectivity. Through the comparison and the discussion of these two research we construct a conceptual framework to analyse a third case from Spain: the case of Rural Promo. Rural Promo is a private consulting company that offers both services to local government institutions and to “rural entrepreneurs”. With a discourse based in Experiential Marketing, this company presents luxury tourism and the commodification of endogenous resources as the solution for rural depopulation and lifestyle depauperate. The discursive and political ecological analysis of Rural Promo consents us to discuss and document it as organisational and financial ‘entexualtization’ of ‘instrumentalisation’ of neorurals, reproducing dominant social relation of production and propriety as well as dominant human-nature relationship. This analysis confirms and further elaborates on the polarised divide between emancipatory-oriented neorurality based not on the autonomous household practices but instead on an instrumentalist vision of nature and the insertion of small rural property within accumulation processes guided by digital platforms (e-commerce) and the logistic sector. The paper concludes by offering reflection on how instrumentalization perpetuates a hegemonic discourse that puts rural areas in service of urban territories and population, fostering the commodification and reification of rural landscape and cultural tradition (through rural tourism and agricultural production).